Presence of rotavirus and free-living amoebae in the water supplies of Karachi, Pakistan - Yousuf, Farzana Abubakar (2017)
Rotavirus and pathogenic free-living amoebae are causative agents of important health problems, especially for developing countries like Pakistan where the population has limited access to clean water supplies. Here, we evaluated the prevalence of rotavirus and free-living amoebae (Acanthamoeba spp., Balamuthia mandrillaris, Naegleria fowleri) in drinking water supplies of Karachi, Pakistan. Six water filtration plants that supply drinking water to the population of Karachi were investigated. Additionally, drinking water samples from households were analyzed for the presence of rotavirus and free-living amoebae. Rotavirus was present in 35% of the water samples collected from water filtration plants; however, domestic tap water samples had a prevalence of only 5%. Out of 20 water samples from filtration plants, 13 (65%) were positive for Acanthamoeba spp., and one (5%) was positive for B. mandrillaris. Out of 20 drinking water samples collected from different areas of Karachi, 35% were positive for Acanthamoeba spp. Rotavirus was detected in 5% of the drinking water samples tested. Overall, these findings showed for the first time the presence of rotavirus, in addition to pathogenic free-living amoebae in drinking water supplies of Karachi that could be an important public health risk for the affected population.